E-Magazine Based on Augmented Reality Digestive as Digital Learning Media for Learning Interest - Zulfarina, Zulfarina; Syafii, Wan; Putri, Deka Gusnia (Journal of Education Technology, 2021)
The obstacle faced in the learning process so far is the low interest in student learning. Many factors affect interest in learning, one of which is the lack of variety of teaching materials or learning media used by teachers in schools. The use of augmented reality (AR) in education is an important topic of research although its use is still in its infancy. The purpose of this research is to develop learning media, AR-based e-magazine to increase students' interest in learning high school students, on the material of the digestive system. The development of the e-magazine is carried out using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The parameters in this study are the quality of the e-magazine and interest in learning. Testing interest in learning is done using an interest questionnaire given to students for the control class consisting of 36 students and the experimental class consisting of 36 students. The results of the development of AR-based e-magazines are relatively good. This can be seen from the validation results with a very valid category. Based on the didactic aspect, a score of 3.82 was obtained in the very valid category, the constructive aspect was 3.85 in the very valid category and the technical aspect was 3.78 in the very valid category. The results showed that the use of AR-based e-magazines increased interest in learning. Interest in learning obtained a score of 0.342 in the high category. Thus, it can be concluded that the use of AR-based e-magazines as digital learning media can be used in the learning process.Â